ANALISIS RISIKO PRODUKSI USAHATANI PADI LADANG DI DESA NGGELA KECAMATAN WOLOJITA KABUPATEN ENDE - Willybrordus Lanamana (Agriculture Faculty of Flores University, 2018)
This study aims to analyze the risk of field rice farming in the dry season and rainy season and the influence of the use of production inputs on the risk of field rice production. The research was conducted in Nggela village with consideration. a) is a dryland village with the main food commodities of paddy rice Field rice farmers in Nggela village as many as 53 farmers, all farmers were studied to get the data and information needed. Analysis of the data used is the coefficient of variation. This analysis is a measure of relative risk obtained by dividing the standard deviation with the expected value. . The magnitude of the influence of input use on production risk was analyzed using multiple linear regression, the production function used was the Cobb Douglass production function beginning with the classical assumption test. The results of the analysis show that the risk of producing paddy rice farming in the rainy season is lower than in the dry season. The results of the t-test analysis show that not all independent variables have a significant effect on the dependent variable. Variables that are not influential are labor variables. Data in the field shows that the workmanship in Nggela village is still familiar with the pattern of cooperation, so that a lot or a little workforce is used that does not affect the risk of production. In the variables of land, seeds, fertilizers, and pesticides, there is a significant and negative sign, this means that any additional land area, seeds, fertilizers and pesticides will reduce the risk of field rice production.